Environmental-oriented development of enterprises of agricultural industry and advanced training of personnel in agricultural environmental management - Yu. D. Vishnyakov; S. P. Kiseleva; L. V. Makolova; V. V. Pham; T. T. Vu Huong (Управление)
The directions of the ecological-oriented development of enterprises of the agro-industrial complex have been analyzed through the implementation of the principles of rational resource consumption. The purpose of the article is to form the scientific basis for the effective use of non-renewable resources by enterprises of the agro-industrial complex in modern economic conditions. A study has been conducted on the causes of waste accumulation in agricultural enterprises and the stages of the greening mechanism of the enterprise functioning have been analyzed. The mechanism of greening the functioning of an enterprise has been considered on the basis of an analysis of the stages, which implies the consistent introduction of technologies and equipment, which makes it possible to reduce the negative impact of agricultural enterprises on the environment.On the basis of the developed general strategy of the enterprise in the field of resource consumption, two models of resource management of an agricultural enterprise have been presented through the use of insourcing and outsourcing tools. The model using insourcing tools assumes the reorientation of the company’s own assets, that are not used in production activities for the cleaning and processing of secondary resources. The model with the use of outsourcing tools assumes the involvement of third-party organizations for the collection and processing of waste in secondary resources. The range of effective implementation of the proposed models in the activities of an agricultural enterprise has been determined. The importance of advanced management training in the field of agricultural economics in the interests of sustainable development of the agro-industrial complex has been denoted and proposals from the State University of Management (SUM) in this area have been presented. The Department of Environmental Management and Environmental Safety has proposed the preparation of masters for the implementation of all activities stipulated by the educational standard in the field of agro-ecological management. The structure of the proposed educational program “Agroecological Management” contains disciplines (modules) of a theoretical and applied nature, that are relevant for the study by specialists of the agro-industrial complex in accordance with the need to solve modern environmental problems.